REQUIREMENTS FOR BUDGETING SYSTEM AND ITS FUNCTIONS - O. Ageeva; E. Potapova (Вестник университета)
The article is devoted to the study of such an important element of the company as budgeting, which recently used Russian companies. In the process of studying it has been identified the basic requirements for budgeting and planning, such as the budget of revenues and expenditures, the cash flow budget, the budgeted balance sheet. Also the basic functions of budgeting that help to increase the company efficiency in the market.